2022
DOI: 10.1002/slct.202201534
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Dopamine Detection using a Fe/Fe3O4@C Composite derived from a Metal‐Organic Framework

Abstract: In this paper, a novel composite of Fe/Fe 3 O 4 @C is synthesized by taking a Fe-metal-organic framework (Fe-MOF) as precursor template. Different treating temperature (450, 550, 650 and 750 °C) were carried out to investigate the composite of calcined products. The Fe/Fe 3 O 4 @C -650 modified glassy carbon electrode (Fe/Fe 3 O 4 @C -650 GCE) shows good electrocatalytic activity towards dopamine (DA) oxidation. Three electrochemical measuring methods of cyclic voltammetry (CV), differential pulse voltammetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Varieties of strategies were designed based on abundant nanoparticles (single/multi‐ metals, metal oxides, metal sulfides, etc.) for fabrication electrochemical sensors [1–5] . According to the previous results, [6–8] the shape has a larger proportion than size in determining the catalytic activity of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Varieties of strategies were designed based on abundant nanoparticles (single/multi‐ metals, metal oxides, metal sulfides, etc.) for fabrication electrochemical sensors [1–5] . According to the previous results, [6–8] the shape has a larger proportion than size in determining the catalytic activity of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 92%
“…for fabrication electrochemical sensors. [1][2][3][4][5] According to the previous results, [6][7][8] the shape has a larger proportion than size in determining the catalytic activity of metal nanoparticles. Metallic nanocrystals have been prepared in a variety of different shapes for acquiring sensitivity sensors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Thus, it is significance to devise an efficient DA detection means. 23,24 So far, there have been some reports on the detection of dopamine on the basis of composites composed by different MOFs and carbon materials as electrode materials. 25,26 For example, Lu and his colleagues also reported that Co 3 O 4 /FeCo 2 O 4 modified glassy carbon electrode for dopamine detection could detect the concentration of dopamine in the range of 0.1-250 μM with high sensitivity (0.04587 μM).…”
mentioning
confidence: 99%